2005
DOI: 10.1097/01.gim.0000182876.57766.2d
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and molecular evaluation of 241 small supernumerary marker chromosomes: Cooperative study of 19 Italian laboratories

Abstract: Purpose: We evaluated the experiences of 19 Italian laboratories concerning 241 small supernumerary marker chromosomes (sSMCs) with the aim of answering questions arising from their origin from any chromosome, their variable size and genetic content, and their impact on the carrier's phenotype. Methods: Conventional protocols were used to set up the cultures and chromosome preparations. Both commercial and homemade probes were used for the fluorescent in situ hybridization analyses. Results: A total of 113 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
20
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 21 publications
9
20
1
1
Order By: Relevance
“…For those cases (Table 1), we find 72 sSMC inherited from the mother versus 30 sSMC inherited from the father, which is similar to the 2.4:1 ratio suggested in the paper by Dalprà et al 1 for the parental origin of sSMC. As detailed in Table 1, this ratio is more expressed in sSMC derived from non-acrocentric chromosomes.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…For those cases (Table 1), we find 72 sSMC inherited from the mother versus 30 sSMC inherited from the father, which is similar to the 2.4:1 ratio suggested in the paper by Dalprà et al 1 for the parental origin of sSMC. As detailed in Table 1, this ratio is more expressed in sSMC derived from non-acrocentric chromosomes.…”
supporting
confidence: 71%
“…As detailed in Table 1, this ratio is more expressed in sSMC derived from non-acrocentric chromosomes. The data presented here is independent of that of Dalprà et al, 1 as there were no details available on their individual patients.…”
mentioning
confidence: 81%
“…This rate is similar for the overall population [~70% according to (3)]. Also it was not unexpected that sSMC [15] was the most frequently observed (4,8). However, the sSMC [14] rate in the infertile patients from the present study was, at 15%, ~4 times higher than in all sSMC cases studied for their chromosomal origin (3,4,8) (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…Several mechanisms seem to be involved here. (i) It has been shown repeatedly (12,15) that sSMC are more likely to be carried forward through the maternal line, thus, selection for gametes without an additional extra chromosome during oogensis can be postulated [for more details see also (12); for centromeric drive see (16)]. (ii) It has also been suggested that any kind of chromosomal aberration can reduce the ability of correct chromosomal pairing during meiosis I (1), which can cause fertility problems especially in males (17).…”
Section: Fertility Problems In Ssmc Carriers and Evolutionary Effectsmentioning
confidence: 99%
“…In our case, the sSMC was also derived from chromosome 22 and a normal phenotype was observed. Although some studies provided indications concerning the pathologic phenotype and the risk accordingly associated with an sSMC (Warburton, 1991;Crolla, 1998), the published data still do not allow any definite conclusions to be drawn concerning karyotype-phenotype correlations (Dalprà et al, 2005).…”
Section: Discussionmentioning
confidence: 99%